2019
DOI: 10.1590/1678-4685-gmb-2017-0260
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome duplication and hemoglobin differentiation traits between allopatric populations of Brazilian Odontophrynus americanus species complex (Amphibia, Anura)

Abstract: Two allopatric populations of Brazilian diploid and tetraploid Odontophrynus americanus species complex, both from São Paulo state, had their blood hemoglobin biochemically analyzed. In addition, these specimens were cytogenetically characterized. Biochemical characterization of hemoglobin expression showed a distinct banding pattern between the allopatric specimens. Besides this, two distinct phenotypes, not linked to ploidy, sex, or age, were observed in adult animals of both populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…This hypothesis was further supported by data on erythropoiesis and the transcription of DNA coding for hemoglobin in 2n and 4n O. americanus, which revealed that the 4n cells have only 30% more hemoglobin and 25-30% more ribosomes that the 2n cells (Cianciarullo et al, 2000). Further studies on hemoglobin traits between allopatric populations of O. americanus 4n showed differences related to the process of diversification (Cianciarullo et al, 2019) Electron microscope studies showed that there are lower number of nuclear pore complexes (NPC) in the 4n with changes in the transport of products to the cytoplasm (Maul et al, 1980). Also, description by electron microscopy of complex aggregates of neighboring NPC in the 4n species may be related to a lower metabolic activity (Beçak and Fukuda-Pizzocaro, 2007).…”
Section: Gene Regulation In Autotetraploid Anuransmentioning
confidence: 73%
“…This hypothesis was further supported by data on erythropoiesis and the transcription of DNA coding for hemoglobin in 2n and 4n O. americanus, which revealed that the 4n cells have only 30% more hemoglobin and 25-30% more ribosomes that the 2n cells (Cianciarullo et al, 2000). Further studies on hemoglobin traits between allopatric populations of O. americanus 4n showed differences related to the process of diversification (Cianciarullo et al, 2019) Electron microscope studies showed that there are lower number of nuclear pore complexes (NPC) in the 4n with changes in the transport of products to the cytoplasm (Maul et al, 1980). Also, description by electron microscopy of complex aggregates of neighboring NPC in the 4n species may be related to a lower metabolic activity (Beçak and Fukuda-Pizzocaro, 2007).…”
Section: Gene Regulation In Autotetraploid Anuransmentioning
confidence: 73%
“…f. that the hemoglobin patterns of allopatric populations of Brazilian 2n and 4n O. americanus indicate that speciation does not require geographic barrier [61];…”
Section: Discussionmentioning
confidence: 99%
“…Herein lays the importance of combining multiple evidences of diagnostic traits. This is especially true for the genus Odontophrynus, for which there are several cryptic species (e.g., Rosset et al 2006Rosset et al , 2021Cianciarullo et al 2019), and lack of genetic, acoustic, and larval data for several populations (see Rocha et al 2017;Martino et al 2019;Rosset et al 2021).…”
Section: Introductionmentioning
confidence: 99%